Development Of Post-Processing Technique For Metal Artefacts Reduction In The Presence Of Contrast Media In Ct Imaging - Yusob, Nur Diana Mohamad (2018)
Artefacts arising from metallic implant in CT imaging had been a concern in obtaining an optimal image quality. The objective of this research is to develop the post-processing technique to reduce the severity of metal artefacts from orthopaedic screw in the presence of contrast media in abdominal CT imaging. Identification of CT images within or near metallic implants should be predicted by imaging, the assessment of disease would be refined, allowing better image analysis of patient for early detection and prevention of acute disease events. This study is performed by using a water-based abdomen phantom of diameter 32 cm (adult body size).